Validation of Multiparametric Ultrasonography Criteria with Digital Subtraction Angiography in Carotid Artery Disease: A Prospective Multicenter Study - Barlinn, Kristian; Rickmann, Henning; Kitzler, Hagen; Krogias, Christos; Strohm, Henning; Abramyuk, Andrij; Barlinn, Jessica; Siepmann, Timo; Rabahi, Ali; Graehlert, Xina; Schwanebeck, Uta; Winzer, Simon; Arnold, Sebastian; Moennings, Peter; Pallesen, Lars-Peder; Bodechtel, Ulf; Mudra, Harald; Linn, Jennifer; Reichmann, Heinz; Alexandrov, Andrei V.; Gahn, Georg; Weiss, Norbert; Puetz, Volker (Ultraschall in der Medizin - European Journal of Ultrasound, 2018)
Purpose The German Society of Ultrasound in Medicine (DEGUM) recently revised its multiparametric criteria for duplex ultrasonography (DUS) grading of internal carotid artery (ICA) disease. We determined the diagnostic accuracy of the revised DEGUM criteria for ultrasonography grading of ICA disease in a prospective multicenter study.Materials and Methods We evaluated consecutive patients who underwent digital subtraction angiography of the extracranial carotid arteries at four tertiary care hospitals. Blinded investigators graded ICA disease according to DEGUM-recommended ultrasonography criteria and calculated NASCET-type percent stenosis from angiography images. Endpoints included overall classification accuracy, prediction of clinically relevant disease categories and between-test agreement in the continuous range of percent stenosis.Results A total of 121 patients (median age: 69 [IQR, 16] years; 74 % men; median time between DUS and angiography: 1 day [IQR, 2]) provided 163 DUS-angiography carotid artery pairs. The classification accuracy of the DEGUM criteria to predict stenosis within 10 % increments as compared to angiography was 34.9 % (95 % CI, 28.0 – 42.6). The sensitivity of DUS for the detection of moderate (50 – 69 %) and severe (70 – 99 %) stenosis was 35 % and 81 %, with an overall accuracy of 73 % and 74 %, respectively. The specificity was 89 % and 69 %, respectively. Considering the continuous spectrum of the disease (0 – 100 %), the Bland-Altman interval limit of agreement was 51 %.Conclusion At laboratories experienced with ultrasound grading of the extracranial ICA, the revised DEGUM multiparametric ultrasonography criteria do not eliminate the need for a confirmatory test for the identification of clinically relevant grades of the disease.
Keywords: angiography; ultrasound; carotid artery disease; diagnostic testing